Is the Energy Cost of Rowing a Determinant Factor of Performance in Elite Oarsmen? - Blervaque, Léo; Bowen, Maximilien; Chatel, Benjamin; Corbex, Emilio; Dalmais, Etienne; Messonnier, Laurent A. (Frontiers in Physiology, 2022)
In elite oarsmen, the rowing ergometer is a valuable tool for both training and studying rowing performance determinants. However, the energy cost of rowing, often reported as determinant of performance, has never been described for ergometer rowing. Therefore, this study aimed to characterize the energy cost of ergometer rowing (ECR) in elite oarsmen, its contribution to 2000 m performance and its determinants. This study was conducted on 21 elite oarsmen from the French national team. It included an incremental exercise test up to exhaustion and an all-out performance test over 2000 m, both conducted on a rowing ergometer. Gas exchange analysis was performed to calculate oxygen uptake and substrate utilization rate. Whole blood lactate concentrations during the incremental test were obtained from the earlobe. During the incremental test, ECR displayed a significant linear increase up to a plateau reached at a mean rowing speed of 5.23 ± 0.02 m.s-1. The ECR values at 300 W, 350 W and 400 W were positively correlated with performance expressed as the time required to perform the 2000 m distance on the rowing ergometer. The same ECR values were found to be significantly related to fat oxidation (expressed in percentage of total energy supply) and blood lactate concentrations. This study provides the first description of ECR and of its relationship to exercise intensity on the rowing ergometer in elite oarsmen. ECR appeared to be a factor of performance and interestingly was related to energy supply from fat and blood lactate concentrations.